About explicit factorization of some classes of non-rational matrix functions - Conceição, Ana C. (2020)
We construct an algorithm that allows us to determine an effective canonical factorization of some non-rational matrix-valued functions. For those matrix-valued functions whose entries can be represented through a innerouter factorization (when the outer function is rational) it is shown that its explicit factorization can be obtained through the solutions of two non-homogeneous equations.